Anthropogenic changes of the Boloyso Lake ecosystem and ways of its restoration - Vlasov, Boris P.; Samoilenka, Vera M.; Hryshchankava, Natallia D. (Journal of the Belarusian State University. Geography and Geology, 2017)
Article is devoted to the analysis of changes in the Boloyso Lake ecosystem under the influence of anthropogenic load from 1948 to 2015, and development of methods for its restoration. The Boloyso Lake is located in Braslavsky district of the Vitebsk region of Republic of Belarus in the center of lakes’ system of National park «Braslavskye ozera» is a good example of rapid degradation of an ecosystem under the influence of a powerful point source of biogenic elements. Dynamics of hydrochemical and hydrobiological indicators demonstrating decrease in rates of lake eutrophication is considered in the article. Need of holding special events, in view of high pollution of water and superficial horizon of sediments of the lake is proved. The technologies of restoration of the lake including external (ecological arrangement of watershed, control of sources of biogenic elements at watershed) and internal measures (aeration, removal of sediments, biomanipulations, etc.) are presented. The schematic diagram of restoration technology for the lake is provided.
Keywords: the Boloyso Lake; anthropogenic load; eutrophication; restoration technologies